Navigating challenges in spatio-temporal modelling of Antarctic krill abundance: Addressing zero-inflated data and misaligned covariates - André Victor Ribeiro Amaral; Adam M. Sykulski; Sophie Fielding; Emma Cavan (Spatial Statistics, 2025)

When to add a new process to a model – and when not: A marine biogeochemical perspective - Adrian P. Martin; Angela Bahamondes Dominguez; Chelsey A. Baker; Chloé M.J. Baumas; Kelsey M. Bisson; Emma Cavan; Mara Freilich; Eric Galbraith; Martí Galí; Stephanie Henson; Karin F. Kvale; Carsten Lemmen; et al. (Ecological Modelling, 2024)

Safeguarding marine life: conservation of biodiversity and ecosystems - Delphi Ward; Jessica Melbourne-Thomas; Gretta T. Pecl; Karen Evans; Madeline Green; Phillipa C. McCormack; Camilla Novaglio; Rowan Trebilco; Narissa Bax; Madeleine J. Brasier; Emma L. Cavan; Graham Edgar; et al. (Reviews in Fish Biology and Fisheries, 2022)
Marine ecosystems and their associated biodiversity sustain life on Earth and hold intrinsic value. Critical marine ecosystem services include maintenance of global oxygen and carbon cycles, production of food and energy, and sustenance of human wellbeing. However marine ecosystems are swiftly being degraded due to the unsustainable use of marine environments and a rapidly changing climate. The fundamental challenge for the future is therefore to safeguard marine ecosystem biodiversity, function, and adaptive capacity whilst continuing to provide vital resources for the global population. Here, we use foresighting/hindcasting to consider two plausible futures towards 2030: a business-as-usual trajectory (i.e. continuation of current trends), and a more sustainable but technically achievable future in line with the UN Sustainable Development Goals. We identify key drivers that differentiate these alternative futures and use these to develop an action pathway towards the desirable, more sustainable future. Key to achieving the more sustainable future will be establishing integrative (i.e. across jurisdictions and sectors), adaptive management that supports equitable and sustainable stewardship of marine environments. Conserving marine ecosystems will require recalibrating our social, financial, and industrial relationships with the marine environment. While a sustainable future requires long-term planning and commitment beyond 2030, immediate action is needed to avoid tipping points and avert trajectories of ecosystem decline. By acting now to optimise management and protection of marine ecosystems, building upon existing technologies, and conserving the remaining biodiversity, we can create the best opportunity for a sustainable future in 2030 and beyond.

Commercial fishery disturbance of the global ocean biological carbon sink - Emma L. Cavan; Simeon L. Hill (Global Change Biology, 2022)
Plankton drive a major sink of carbon across the global oceans. Dead plankton, their faeces and the faeces of plankton feeders, form a huge rain of carbon sinking to the seabed and deep ocean, reducing atmospheric CO 2 levels and thus helping to regulate the climate. Any change in plankton communities, ecosystems or habitats will perturb this carbon sink, potentially increasing atmospheric CO 2 . Fishing is a major cause of ocean ecosystem disturbance affecting all trophic levels including plankton, but its potential impact on the carbon sink is unknown. As both fisheries and the carbon sink depend on plankton, there is spatial overlap of these fundamental ecosystem services. Here, we provide the first global maps of this spatial overlap. Using an upper quartile analysis, we show that 21% of the total upper ocean carbon sink (export) and 39% of fishing effort globally are concentrated in zones of intensive overlap, representing 9% of the ocean surface area. This overlap is particularly evident in the Northeast Atlantic suggesting this region should be prioritized in terms of research and conservation measures to preserve the high levels of sinking carbon. Small pelagic fish dominate catches here and globally, and their exploitation could reduce important faecal pellet carbon sinks and cause trophic cascades affecting plankton communities. There is an urgent need to recognize that, alongside climate change, fishing might be a critical influence on the ability of the ocean to sequester atmospheric CO 2 . Improved understanding of this influence, and how it will change with the climate, will be important for realizing a sustainable balance of the twin needs for productive fisheries and strong carbon sinks.

“Sinking dead”—How zooplankton carcasses contribute to particulate organic carbon flux in the subantarctic Southern Ocean - Svenja Halfter; Emma L. Cavan; Philip Butterworth; Kerrie M. Swadling; Philip W. Boyd (Limnology and Oceanography, 2022)
Zooplankton carcasses are an important, yet understudied, pathway of the biological gravitational pump. To understand their contribution to the downward carbon flux in the subantarctic, carcasses of the copepod Neocalanus tonsus were analyzed for carbon content, microbial remineralization rates, and sinking velocities. In addition, the sensitivity of carcass flux to varying mortality, microbial turnover, and sinking velocity rates was analyzed and compared to carbon flux measurements from sediment traps. Microbial decomposition rates (between 0.02 and 0.16 d −1 ) were comparable to those of marine snow, highlighting the importance of carcasses as microbial hotspots. High sinking velocities (730 ± 182 m d −1 ) suggest that particulate organic carbon flux to the deep ocean is substantial. Carcass flux is sensitive to a change in sinking velocity but appears less sensitive to fluctuations in microbial decomposition rate. More research on zooplankton mortality and the factors that influence carcass sinking through the water column is needed to quantify the carcass‐mediated carbon export and enable their inclusion in marine ecosystem and biogeochemical models.

The Role of Zooplankton in Establishing Carbon Export Regimes in the Southern Ocean – A Comparison of Two Representative Case Studies in the Subantarctic Region - Svenja Halfter; Emma L. Cavan; Kerrie M. Swadling; Ruth S. Eriksen; Philip W. Boyd (Frontiers in Marine Science, 2020)

Overcoming the Obstacles Faced by Early Career Researchers in Marine Science: Lessons From the Marine Ecosystem Assessment for the Southern Ocean - Madeleine J. Brasier; Stacey McCormack; Narissa Bax; Jilda A. Caccavo; Emma Cavan; Jessica A. Ericson; Blanca Figuerola; Alyce Hancock; Svenja Halfter; Nicole Hellessey; Juan Höfer; Peter S. Puskic; et al. (Frontiers in Marine Science, 2020)

Changing Biogeochemistry of the Southern Ocean and Its Ecosystem Implications - Sian F. Henley; Emma L. Cavan; Sarah E. Fawcett; Rodrigo Kerr; Thiago Monteiro; Robert M. Sherrell; Andrew R. Bowie; Philip W. Boyd; David K. A. Barnes; Irene R. Schloss; Tanya Marshall; Raquel Flynn; et al. (Frontiers in Marine Science, 2020)

Sinking Organic Particles in the Ocean—Flux Estimates From in situ Optical Devices - Sarah Lou Carolin Giering; Emma Louise Cavan; Sünnje Linnéa Basedow; Nathan Briggs; Adrian B. Burd; Louise J. Darroch; Lionel Guidi; Jean-Olivier Irisson; Morten H. Iversen; Rainer Kiko; Dhugal Lindsay; Catarina R. Marcolin; et al. (Frontiers in Marine Science, 2020)